PENERAPAN MODEL PEMBELAJARAN SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI KEUANGAN - Nely Hartika; Restu Ayu Ismayanti (FKIP, Universitas Banten Jaya, 2018)
This study was aimed to find out how the application of scramble learning model in class XI SMK Pasundan 1 Serang City and found out how the learning outcomes of students.This research used classroom action research method consisting of two cycles. Each cycle consists of four stages: planning, execution, observation and reflection. The subjects of this study were students of class XI SMK Pasundan 1 Serang City with 39 students and subject teacher as a team of collaborator.The results of this study indicateed that the scramble learning model could improve student learning outcomes because in the first cycle, from 39 students who managed to score above the KKM was 79,35% or 33 students, while in the second cycle increased to 90,25%.